Medical device materials VI : proceedings from the Materials & Processes for Medical Devices Conference 2011, August 8-10, 2011, Hilton Minneapolis, Minneapolis, Minnesota, USA (ASM International, 2013)
This volume includes contributions from the world's foremost experts from academia, industry, and national laboratories involved in cardiac, vascular, neurological, and orthopaedic implants, dental devices, and surgical instrumentation/devices. --